Community Resistance to Online Learning Policies During Covid-19 Pandemic in Education: Resistensi Masyarakat terhadap Kebijakan Pembelajaran Daring di Masa Pandemi Covid-19 pada Pendidikan - Wigati, Indah; Yuniar; Lestari, Weni (Universitas Muhammadiyah Sidoarjo, 2023)
The online learning policy, which is believed to be the only way out of overcoming learning and accelerating the end of the transmission of the Covid-19 virus, has been widely rejected. In Indonesia, various community groups do not support and even protest the implementation of online learning. This paper aims to analyze the forms and factors of community resistance to online learning policies. This study uses a qualitative descriptive technique. The discourse of denial in online news forms the basis for the findings of this study. Data collection was done by interview and observation. Informants in this study were parents, teachers, and students. The data obtained were analyzed using the stages of data reduction, data presentation, and drawing conclusions and verification. The results showed that the refusal was based on the inhibited state-people communication and the readiness to face online learning that was not maximized. People are not involved in every stage of the policy and tend to be required to comply with their capabilities and limitations, both in implementation and in supporting learning facilities and infrastructure. This rejection was caused by structural factors rooted in the tension in the relationship between the people and the state. So it is necessary to build cultural communication to eliminate psychological tension between the people and the state. The open nature of both parties will be a reinforcement in solving various problems and have a positive impact on the order of people's.